Formation, Growth, and Adaptive Change in Marketing Systems. (September 2015) - Layton, Roger A.
The article outlines an integrated theoretical framework identifying the causal processes underlying formation, growth, and adaptive change in marketing systems. Beginning with the co-evolution of behaviors, beliefs, and social practices that initiate innovative change in marketing systems, it integrates three theoretical frameworks drawn from analytical sociology, organization and social movement theory, and from macromarketing to show how and why economic exchange in and between human communities leads to formation, growth, and adaptive change in marketing systems. The theory of social mechanisms identifies the means whereby actions taken by individuals and entities participating in a marketing system will regularly produce over time the collective outcomes that characterize a marketing system. The theory of strategic action fields explains how these actions, engendered by competition between participants for material and status rewards in the social action field associated with a marketing system, lead to internal and external change in a marketing system. The theory of marketing systems identifies the tangible and intangible elements of structure and function in marketing systems that emerge from the interaction of social mechanisms and action fields over time and that are found in every human community. As marketing systems form, grow, and change they become part of the immediate environment in turn influencing the actions of individuals, groups and entities, as well as adjacent marketing systems, shaping on-going co-evolution, the operation of social mechanisms, and the strategic choices made by actors in action fields. The Mechanism, Action, Structure (MAS) framework of theory is dynamic, explores causation, links micro choices and macro structures, focusses on processes rather than variables, and links macromarketing with cognate social sciences in an understanding of economic exchange in human communities.